Theory of Planned Behaviour: Accounting Pre-Service Teacher's Intention in Knowledge Sharing - Sri Sumaryati; Wulan Romadhoni; Binti Muchsini (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the level of knowledge sharing of students of Accounting Education at one of the universities in Central Java. This research is a quantitative survey research with descriptive statistical data analysis techniques. The populations in this study were all active students of the Accounting Education Study Program in the 2018-2020 class, totalling 247 students. The sampling technique used is proportional random sampling with a sample of 149 students. The data collection technique used is a questionnaire. This study measures the level of knowledge sharing using the Knowledge Sharing Behavior Scale (KSBS) instrument from Yi with indicators of written contribution, organizational communication, personal interaction, and community practice. This study concludes that the level of knowledge sharing of students of Accounting Education can be categorized as inferior. This refers to the TCR result of 63.49%. Lecturers in the learning process can support all students and create a classroom atmosphere that supports knowledge-sharing behaviour. Students must also be aware of the importance of knowledge-sharing behaviour to achieve learning objectives.